Eksistensi Motivasi dalam Meningkatkan Potensi Personal dalam Perspektif Al-Qur’an dan Hadis - Muhammad Sapii Harahap; Salsa Ikhlasiyah; Nunzairina Nunzairina (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2022)
The main sources of Islamic references are the Qur'an and Hadith. These two sources of law provide encouragement to each individual to always try to increase the potential in him, both the potential is beneficial for life in this world and beneficial for life in the hereafter. With the ultimate goal of achieving behavior change, motivation is needed. Motivation is one of the elements that encourage a person to need to increase his potential. Motivation has an important role and determines a person's success in achieving the goals he sets or realizing his hopes. This research uses literature research (library research) or literature research with a qualitative approach, that data comes from books, journals, books, and other scientific writings. In collecting data used documentation techniques. The sources of data collected in this study consisted of primary and secondary data sources. The primary data from this research are several verses of the Qur'an, the hadith of the prophet and the book of interpretation. The secondary data in this study are in the form of supporting documents in this study such as books, articles, and journals. Extrinsic and intrinsic motivation have a positive influence as an individual driver in developing his potential. There are several verses of the Koran and the hadith of the prophet contained in it extrinsic and intrinsic motivation.